PEMBELAJARAN TATA BAHASA INGGRIS SECARA KOMUNIKATIF DENGAN PENYAJIAN INDUKTIF DAN PENGINTEGRASIAN KETERAMPILAN BERBAHASA: STUDI KASUS DI KELAS BAHASA INGGRIS I DI IAIN RADEN FATAH PALEMBANG - Annisa Astrid (Ta'dib: Jurnal Pendidikan Islam, 2011)
AbstractTeaching grammar has been regarded as prominence in teaching a language where there are some different views of how to teach it. Recently, with the introduction of Communicative Language Teaching, teaching grammar is emphasized on experiential learning and communicative goals. For these reasons the writer tried to implement inductive approach in Bahasa Inggris class, where all the students are from Non English Department. In inductive approach, the learners study examples and from these examples derives an understanding of the rule. the writer also presented the grammar integrated with four language skills (speaking, listening, reading, and writing), where the writer paid more attention to enabling students to work with the target language during the lesson and communicate in it by the end of it.. In totally 14 meetings, the teacher applied inductive approach in presenting the materials and gave all exercises integratedly to four language skills (speaking, writing, reading and listening). The data were collected by means of T-Test. From the results of the T-test, it can be seen that the T value is 5,193, with the significance value 0,001. T value is more than T table ,2,042 . It can be interpreted that there is a significant difference between the students’ achievement in grammar before the treatment and after the treatment by using inductive approach and applying the activities that integrates grammar into four language skills. It was also found that the students were enthusiastic along the teaching and learning processes by implementing inductive approach. Keywords: inductive, communicative language teaching